SOURCE ROCK EVALUATION BASED ON GEOCHEMICAL DATA AND 1D BURIAL HISTORY MODELLING IN X BLOCK, SOUTH SUMATERA BASIN - Dwi Putri, Tiara Intan; Pramudito, Dimas; Sendjaja, Yoga Andriana; Ilmi, Nisa Nurul (Journal of Geological Sciences and Applied Geology, 2023)
The study was conducted in the South Sumatra Basin using geochemical data consisting of three exploration wells to determine geochemical characteristics such as richness, quality, maturity, and the depositional environment of the source rock. Additionally, the study delved into the one-dimensional burial history of the study area. Subsequent phases of the research involved the analysis of three crude oil samples and three rock extract samples. This analytical process encompassed the utilization of gas chromatography (GC) and gas chromatography - mass spectrometry (GC-MS) data. By scrutinizing the biomarker parameters extracted through GC and GC-MS, the research sought to discern the specific characteristics of the depositional environment for each sample and establish a correlation between the source rock and the crude oil. Based on source rock evaluation, the three source rock wells are potential source rock. Based on biomarker analysis, TAN-1 and TAN-2 have an oxic terrestrial/fluvio-deltaic characteristics with a dominantly higher plant contributions. Samples RA-12, RA-17, and RA-61 have a suboxic – anoxic fluvio-deltaic characteristics with contributions of dominantly marine algae. The oil samples taken from these wells have a negative correlation with the source rock samples. Maturity analysis of the TAN-1, TAN-2, and TAN-3 wells is still in its immature phase based on one-dimensional burial history modeling.